2009
DOI: 10.1152/ajprenal.90493.2008
|View full text |Cite
|
Sign up to set email alerts
|

Activation of renal renin-angiotensin system in upstream stimulatory factor 2 transgenic mice

Abstract: S. Activation of renal renin-angiotensin system in upstream stimulatory factor 2 transgenic mice. Am J Physiol Renal Physiol 296: F257-F265, 2009. First published November 12, 2008 doi:10.1152/ajprenal.90493.2008.-Previously we demonstrated that upstream stimulatory factor 2 (USF2) transgenic (Tg) mice developed nephropathy including albuminuria and glomerular hypertrophy, accompanied by increased transforming growth factor (TGF)-␤ and fibronectin accumulation in the glomeruli. However, the mechanisms by whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 43 publications
2
16
0
Order By: Relevance
“…The lack of TGF-␤1 gene stimulation in the USF1 Ϫ/Ϫ diabetic kidney likely contributes to the reduction of matrix gene expression of Stimulation of the RAS is a hallmark of diabetic kidney disease, and clinical studies have clearly demonstrated the benefits of inhibiting the RAS in diabetic nephropathy. Our study supports the accumulating evidence (13,26,37) that the key genes renin and angiotensinogen are likely the initial drivers of stimulating RAS activity in diabetic kidney disease. There was a Ͼ10-fold induction of angiotensinogen and a Ͼ4-fold induction of renin with diabetes.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The lack of TGF-␤1 gene stimulation in the USF1 Ϫ/Ϫ diabetic kidney likely contributes to the reduction of matrix gene expression of Stimulation of the RAS is a hallmark of diabetic kidney disease, and clinical studies have clearly demonstrated the benefits of inhibiting the RAS in diabetic nephropathy. Our study supports the accumulating evidence (13,26,37) that the key genes renin and angiotensinogen are likely the initial drivers of stimulating RAS activity in diabetic kidney disease. There was a Ͼ10-fold induction of angiotensinogen and a Ͼ4-fold induction of renin with diabetes.…”
Section: Discussionsupporting
confidence: 89%
“…Both genes were close to control levels in the diabetic USF1 Ϫ/Ϫ mice. These data are similar to what was found in the USF2 transgenic mouse as there was increased renin gene stimulation (26). It is therefore likely that USF1 and USF2 both contribute to stimulation of renin and may well act synergistically.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It should be noted that upstream stimulatory factors (USF1 and USF2) have been reported to be involved in TGF-␤ up-regulation by high glucose and diabetic conditions and associated with the pathogenesis of DN (13)(14)(15)56). USFs are also E-box-regulators and have a LZ motif, which is critical for homo-or heterodimerization (16).…”
Section: Tsc-22 Interaction With Tfe3 On Far Upstream E-box Region Enmentioning
confidence: 99%
“…After treatment, cells were harvested and total RNA was extracted using RNeasy mini kit, according to the manufacturer’s instructions (Qiagen, Valencia, Calif., USA). Total RNA was converted to cDNA with murine leukemia virus reverse transcriptase (Promega) and real-time PCR was performed to determine the changes in USF2 and the components of the RAS as described previously [18,21]. Primers were synthesized by Integrated DNA Technologies.…”
Section: Methodsmentioning
confidence: 99%